The principal's leadership in organizational culture development: A case study in the context of community engagement and social environment - Mufidah, Diroyatul (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: This study examines the role of the principal in developing organizational culture at XYZ Junior High School. The organizational culture at this school encompasses religious values, integrity, social interaction, cooperation, and politeness, which are implemented by the principal, teachers, educational staff, and students. Method: The research employs a qualitative approach with a case study method. Data collection techniques include interviews, observations, and documentation. Findings: The findings indicate that the principal performs five main roles: as an individual, educator, leader, manager, and entrepreneur. The principal adopts democratic, visionary, transformational, and bureaucratic leadership styles to foster organizational culture. The development of organizational culture at XYZ Junior High School includes literacy programs, teacher on-duty assignments, women’s studies groups, Qurban learning programs, Friday IKSAN activities (Faith, Cleanliness, Health, and Counseling), as well as forums for discussion and sharing best practices within the learning community. Conclusion: The success of organizational culture development is supported by effective communication, recognition of performance, and the principal's innovation in creating a conducive environment. Challenges include shifting the mindset of school members, which are addressed through supervision, coordination, and incentives. Novelty/Originality of this Study: The research uniquely emphasizes the principal’s entrepreneurial role in education, demonstrating how strategic leadership can drive cultural and operational improvements in schools. This study underscores the importance of the principal's role in building an organizational culture that fosters a productive, harmonious learning environment aligned with contemporary developments.